When 'trust in top management' matters to organisational performance and effectiveness: the impact of senior manager role-modelling and group cohesiveness - Eng, Ngiang Jiang (Curtin University, 2010)
While ‘trust in top management’ matters to organisational performance and effectiveness, low trust in top management remains an issue in many organisations despite their efforts in building trust. The persistence of such problems appears to be largely due to improper approach used in the treatments of trust. While the literature reflects a fair amount of effort directed towards an understanding of trust building process, little research, if any, has been done into three important issues that follow. First, the potential effects of group processes on employee perceptions of management’s trustworthiness. Second, the moderating effects of potential moderators on the relationships between trust in management and important organisational outcomes. Third, the potential impacts of cultural differences on trusting relationships.This research investigates into how organisations can strategise to deal with the persistent problem of low trust in top management. Backed by research evidence, the study provides insights for organisations to deal with this problem through (1) promoting group cohesiveness to improve employee trust in top management; and (2) promoting senior manager role-modelling to minimize the impacts of trust in top management on organisational outcomes.To carry out the research, this study develops a theoretical framework that includes group cohesiveness, top management’s trustworthiness factors, trust in top management, important organisational outcomes (i.e., affective commitment, job satisfaction, turnover intention, and intention-to-return), senior manager role-modelling, and their proposed interrelationships. From the theoretical framework emerges an analytical model which elucidates the theories and empirical evidence underlying the proposed relationships in the theoretical framework, and develops a series of theoretically justified and testable hypotheses to address the research questions/problem.Data collection was administered in two field studies conducted in WesternAustralia (the WA study) and Singapore (the SIN study). In both field studies, the population of interest was employees from a diverse range of industries. Thesampling frame for the WA study comprised ten (10) randomly selected companiesoperating in various industries; and a random sample of employees in a variety ofindustries. For the SIN study, the sampling frame included fifteen (15) randomlyselected companies operating in various industries. Of the 1,500 survey packsdistributed in the WA study, the hypotheses were empirically tested on a final sampleof 305 respondents using multiple regression analysis, simple regression analysis,and subgroup analysis. And, of the 1,000 survey packs distributed in the SIN study,the hypotheses were empirically tested on a final sample of 212 respondents using the same data analysis techniques.Evidence from both the WA and SIN studies consistently concludes, inter alia, that (1) group cohesiveness positively influences employee perceptions of top management’s trustworthiness, which in turn improve trust in top management; and (2) in situations where trust in top management is low, senior manager role-modelling can serve to minimize the impacts that trust in top management has on organisational outcomes, thereby minimizing undesirable impacts on organisational performance and effectiveness. Since the research findings have been replicable across two culturally different countries, their generalisability to other settings is highly possible.Further, the research findings offer several theoretical implications. First, referent of trust (trustee) moderates the trust–antecedent relationships, such that the trust model with two predictors (trustee’s ability, and integrity) is statistically desired for predicting trust in top management, whereas the trust model with three predictors (trustee’s ability, integrity, and benevolence) may be well-suited for predicting trust in other organisational authorities. Second, social context for trust (e.g., groups), in which group processes play a major role in the social construction of trust, must not be neglected in the study of trust. Third, at any level of trust in top management, senior manager role-modelling can serve to improve the levels of desirable outcomes, which in turn enhance desirable impacts on organisational performance and effectiveness. Fourth, study of trust should increase emphasis on potential moderator variables in trust–outcome relationships to enhance accuracy of research findings. Likewise, study of organisational performance and effectiveness should not neglect potential moderator variables that can possibly minimize the strong impacts that trust in top management has on important organisational outcomes, especially for situations with low trust in top management.Fifth, the regression models of trust in top management across culturally different countries may differ significantly due to the differences in valuing top management’s integrity when making judgments about top management’s trustworthiness. Sixth, positive influence of group cohesiveness on employee perceptions of top management’s trustworthiness may not be affected by cross cultural differences. Last but not least, cross cultural differences may not affect the impacts of trust in top management on affective commitment, turnover intention, and intention-to-return. However, they may vary the impacts that trust in top management has on job satisfaction due to the differences in valuing trust in top management when evaluating job experiences or work context.Equally important, the research findings suggest two practical implications. First, considering trust is both an interpersonal and a collective phenomenon, promoting group cohesiveness is important and instrumental in improving trust in top management. In this regard, firms can build group cohesiveness by ways of team building activities, management actions, and use of cohesion messages. Next, when appropriate senior manager role-modelling is lacking, trust in top management is very critical, and is required if high levels of affective commitment, job satisfaction, intention-to-stay, and intention-to-return are to be attained. However, when appropriate senior manager role-modelling exists, trust in top management becomes less critical in terms of affective commitment, job satisfaction, intention-to-stay, and intention-to-return. Some helpful steps for firms to promote senior manager role-modelling include: (1) top management formalizes an organisational value system that is consistent with the organisation’s goals and objectives; (2) top management internalizes the organisational value system as part of senior managers’ character, with role-modelling expert’s guidance; and (3) senior managers ‘role model’ the organisational value system for subordinates, provide an example of exemplary behaviour for subordinates to imitate, and thereby instilling the organisational value system into subordinates such that shared values are internalized in them.